Media Portrayal of GM Science and Citrus Greening in State and National Newspapers - Jeremy D'Angelo; Jason D Ellis Ph.D.; Katherine Burke Ph.D.; Taylor Ruth (Journal of Applied Communications, 2018)
Huanglongbing (HLB), commonly known as citrus greening, is a bacterial disease severely affecting the profitability and continuation of the citrus industry in Florida and is threatening the citrus industry in other states as well. Currently, the disease only can be managed, not cured. Gene-based therapies, such as GM science, have been identified as a viable long-term solution. However, consumer acceptance of genetically modified food is low and their understanding and acceptance of new technologies is largely dependent on what they receive through mass media. Therefore, the purpose of this research is to understand news coverage of both citrus greening and gene modification science. This content analysis studied news articles of either citrus greening or gene modification science in national and state-specific newspapers and identified that while citrus greening is not highly covered by newspapers, it is accurately described via appropriate terminology. Genetic modification science is more commonly a topic of news coverage and is somewhat neutral and balanced in coverage. This research shows that source use in media coverage of gene modification science is balanced, but sources are most commonly chosen from organizations with a directed opinion or position on the topic.
Keywords: Citrus greening; GMO; Content analysis; Agenda Setting Theory; Framing Theory